Echocardiography in the coronary care unit: diagnostic and prognostic impact in comparison with clinical and other indicators - Romano, Silvio; Varveri, Antonio; Aurigemma, Giuseppe; Dagianti, Alessandra; Vitarelli, Antonio; Sciomer, Susanna; Pastore, Luciano Raffale; Penco, Maria; Dagianti, Armando (The American journal of cardiology, 1998)
The clinical arena in which we must consider the role of echocardiography is characterized by 2 fundamental findings: (1) most patients with chest pain and suspected acute myocardial infarction (MI) do not present diagnostic electrocardiograms; and (2) an early and correct diagnosis is necessary to match the patient with the most adequate treatment. Echocardiography may be very useful in the coronary care unit, allowing a correct diagnosis of ischemic heart disease when electrocardiography is unclear, even before the rise of cardiac enzymes is detected. It may also play a role in decision-making for thrombolytic therapy. In addition, echocardiography provides useful information for early risk stratification. In fact, although high-risk patients are well identified by simple clinical or instrumental variables (i.e., Killip classification, enzymatic data, blood–gas analysis, electrocardiogram, etc.), most patients (>60%) are identified as low risk, and several subjects classified into the low-risk groups have a poor prognosis and are not detected using a single variable. In our experience, 2-dimensional echocardiography was able to further stratify between patients of low-risk classes. Therefore, echocardiography plays an important role in the early stratification of acute MI patients, especially in those without signs or symptoms of heart failure.